THE ROLE OF REWARD AS A MODERATION VARIABLE IN THE INFLUENCE OF RESPONSIBILITY AND INITIATIVE ON SALES PERFORMANCE AT PT. BEAUTIFUL GUNA PROSPEROUS MEDAN - Bayu Teta (International Research of Multidisciplinary Analysis, 2023)
This study aims to determine the role of reward as a moderating variable in the influence of responsibility and initiative on sales performance at PT. Guna Indah Makmur Medan. This type of research is quantitative research. The research instrument used in this study was a Likert questionnaire with a measurement scale. The sample in this study were 30 sales people. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, determination test and MRA test. The study's results indicate that partially responsibility and initiative significantly affect sales performance at PT. Guna Indah Makmur Medan, but rewards cannot moderate the effect of responsibility and initiative on sales performance at PT. Guna Indah Makmur Medan